Applications of a Novel Microangioscope for Neuroendovascular Intervention - Srinivasan, V.M.; Lazaro, T.T.; Srivatsan, A.; Cooper, P.; Phillips, M.; Garcia, R.; Chen, S.R.; Johnson, J.N.; Burkhardt, J.-K.; Collins, D.E.; Kan, P. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Visualization in neuroendovascular intervention currently relies on biplanar fluoroscopy and contrast administration. With the advent of endoscopy, direct visualization of the intracranial intravascular space has become possible with microangioscopes. We analyzed the efficacy of our novel microangioscope to enable direct observation and inspection of the cerebrovasculature, complementary to a standard fluoroscopic technique.MATERIALS AND METHODS: Iterations of microangioscopes were systematically evaluated for use in neurodiagnostics and neurointerventions in both live animal and human cadaveric models. Imaging quality, trackability, and navigability were assessed. Diagnostic procedures assessed included clot identification and differentiation, plaque identification, inspection for vessel wall injury, and assessment of stent apposition. Interventions performed included angioscope-assisted stent-retriever thrombectomy, clot aspiration, and coil embolization.RESULTS: The microangioscope was found helpful in both diagnosis and interventions by independent evaluators. Mean ratings of the imaging quality on a 5-point scale ranged from 3.0 (clot identification) to 4.7 (Pipeline follow-up). Mean ratings for clinical utility ranged from 3.0 (aspiration thrombectomy) to 4.7 (aneurysm treatment by coil embolization and WEB device).CONCLUSIONS: This fiber optic microangioscope can safely navigate and visualize the intravascular space in human cadaveric and in vivo animal models with satisfactory resolution. It has potential value in diagnostic and neurointerventional applications.ICADintracranial atherosclerotic diseaseIVUSintravascular ultrasoundOCToptical coherence tomography